INCLUSIVE EDUCATION IN INDONESIA: POLICY ANALYSIS, CHALLENGES, AND HIGH- QUALITY IMPLEMENTATION EFFORTS TOWARDS ACHIEVING ACCESS ANDEDUCATIONAL EQUALITY FOR ALL STUDENTS WITH SPECIAL NEEDS - Siminto; Komari Komari; Fenni Kurniawati Ardah; M. Ali Mauludin; Teguh Pribadi (International Journal of Teaching and Learning, 2023)
In inclusive education, Indonesia stands at a pivotal juncture, striving to balance policy aspirations with on-the-ground realities. This research, encapsulated in the paper "Inclusive Education in Indonesia: Policy Analysis, Challenges, and High- Quality Implementation Efforts towards Achieving Access and Educational Equality for All Students with Special Needs," is a meticulous exploration of the Indonesian context. The study employs a mixed-method approach, seamlessly combining quantitative and qualitative data collection methods. Our findings paint a comprehensive picture of inclusive education in Indonesia, revealing both the promising developments and the formidable challenges that persist. The awareness of inclusive education policies among educators is commendable, with approximately 78% acknowledging their existence. However, a stark contrast emerges in the practical implementation, as only 45% perceive these policies to be effectively executed. Challenges about inadequate resources and support are prominent, with 62% of educators expressing concerns in this regard— additionally, 68% point to a dearth of teacher training and professional development opportunities. On a brighter note, the importance of collaborative teaching and the prevalence of individualized education plans (IEPs) are recognized at 79% and 74%, respectively. The implications of these findings are profound, demanding a holistic approach towards fostering inclusive education. This necessitates effective policy implementation, resource allocation, and teacher training investments. Collaborative teaching and adopting IEPs signify progressive strides towards personalized and higher-quality education. The significance of this research extends beyond academia; it offers a roadmap for policymakers, educators, and stakeholders, charting a course toward a more inclusive, equitable, and just education system.